Visagism: the construction of a unique smile - Clinical case report. (Research, Society and Development, 2020)
Objective: In this way, the objective of the present work is to report a clinical case of oral aesthetic rehabilitation based on the integration of visagism concepts, through ceramic laminates. Methodology: Based on the patient's permission through the Free and Informed Consent Term (ICF) to share her image for due purpose, the present study deals with a clinical case report of a descriptive analytical nature (Pereira et al., 2018), performed at a private clinic in the city of Maceió-AL. Case report: Patient C.A.S., female, 30 years old, came to the clinic, dissatisfied with her smile and how it harmonized with her face. Final considerations: The patient's case was concluded satisfactorily in view of her objectives and based on the aesthetic and harmony assumptions of the smile preached by restorative and aesthetic dentistry and visagism. Therefore, when well-planned dental treatment associated with technological resources and the art of visagism gives the patient improvements in his social life, a unique smile that conveys human values.